2019
DOI: 10.1177/2472555218810323
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Sensorial Neuron-Like Cells for HTS of Novel Analgesics for Neuropathic Pain

Abstract: In this study we developed a new translational phenotypic in vitro model for high-throughput screening (HTS) of novel analgesics for treating neuropathic pain, in order to address the poor translation of traditional recombinant models. The immortalized dorsal root ganglia (DRG) neuron-like F11 cell line was selected based on its phenotype after differentiation. The acquisition of neuronal characteristics was evaluated by measuring the expression of TrkA as a DRG neuron marker ( p < 0.01) as well as by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(66 reference statements)
3
13
0
Order By: Relevance
“…In contrast, the mRNA expression profiles of Nav1.7 and Nav1.8 in the present study were maintained for at least 13 days in vitro, and are consistent with profiles in acutely dissociated adult mouse DRG neurons shown previously [ 32 ]. Additionally, our histological study demonstrated a high percentage of Nav1.8-expressing neurons in combination with Nav1.7 (60–70%) which is consistent with previous observations in DRG tissue [ 2 , 3 , 41 ], wherein 88% of cultured DRG tissue was described as nociceptive. An in-depth characterization of Nav1.7 and Nav1.8 expression in neurochemically distinct nociceptive populations demonstrated an enriched expression of Nav1.7 and Nav1.8 in NF200−/TrkA+ and NF200−/TrkA- adult DRG populations compared to non-nociceptive NF200+/TrkA− subtypes, suggesting preferential expression of these isoforms in peptidergic and non-peptidergic populations [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the mRNA expression profiles of Nav1.7 and Nav1.8 in the present study were maintained for at least 13 days in vitro, and are consistent with profiles in acutely dissociated adult mouse DRG neurons shown previously [ 32 ]. Additionally, our histological study demonstrated a high percentage of Nav1.8-expressing neurons in combination with Nav1.7 (60–70%) which is consistent with previous observations in DRG tissue [ 2 , 3 , 41 ], wherein 88% of cultured DRG tissue was described as nociceptive. An in-depth characterization of Nav1.7 and Nav1.8 expression in neurochemically distinct nociceptive populations demonstrated an enriched expression of Nav1.7 and Nav1.8 in NF200−/TrkA+ and NF200−/TrkA- adult DRG populations compared to non-nociceptive NF200+/TrkA− subtypes, suggesting preferential expression of these isoforms in peptidergic and non-peptidergic populations [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…Substrate integrated microelectrode arrays (MEAs), alternatively, provide non-invasive and long-term measurements recorded simultaneously from a large population of cells. The use of an MEA platform may allow the development of in vitro phenotypic screening assays that utilize cellular excitability for screening potent small molecule inhibitors against “pain” channels and support efforts in identifying analgesic compounds [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]…”
Section: Introductionmentioning
confidence: 99%
“…Fura-2 (Hashemian et al, 2017). FLIPR Calcium-6 (Martinez et al, 2019). Bioluminescence imaging (Hwang et al, 2008).…”
Section: Expression Of Neuronal and Nociceptor-related Receptors And Moleculesmentioning
confidence: 99%
“…Perforated patch clamp (Ambrosino et al, 2019). Membrane potential measurement (Martinez et al, 2019).…”
Section: Expression Of Neuronal and Nociceptor-related Receptors And Moleculesmentioning
confidence: 99%
See 1 more Smart Citation